Social and psychological features of the mental component of the modern hybrid war against Ukraine - N. V. Bobro (Bulletin of Kharkiv National University of Internal Affairs)
The concept of “hybrid war” and its structural elements, to which we added a mental component, have been considered. It is shown that in the course of such a war, “hybrid” means are used as a specific tool for ensuring the success of military intervention with the simultaneous involvement of the population in the conflict, which is carried out in the covered military territory, and misleads the international community with the aim of its desired influence on the said conflict.